The summer before the war [compact disc, unabridged] : a novel - Simonson, Helen (Random House Audio, 2016)
Bestselling author Helen Simonson returns with a splendid historical novel full of the same wit, romance, and insight into the manners and morals of small-town British life as her beloved "Major Pettigrew's Last Stand." It's the summer of 1914 and life in the sleepy village of Rye, England is about to take an interesting turn. Agatha Kent is expecting an unusual candidate to be the school's Latin teacher: Beatrice Nash, a young woman of good breeding in search of a position after the death of her father. Agatha's nephews, meanwhile, have come to spend the summer months, as always, both with dreams of their own. When Hugh is sent to pick up Beatrice from the train station - life, of course, changes. Here, these characters and others we come to love and root for become characters we hope and pray for when the shadow of the Great War looms ever closer to home.